New optical Heisenberg model with timelike optical de Sitter flux density - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2022)
In this manuscript, we construct new model for de Sitter magnetic Lorentz flux for timelike magnetic T- fiber by de Sitter frame in S-1(2). Then, we present new optical illustrations of timelike magnetic T- fiber by using polarized wave beam fields. Thus, we determine spherical geometric flux surface by spherical flux density. Also, we present new construction for timelike magnetic T-fiber by Heisenberg Sitter ferromagnetic model. Finally, we demonstrate some illustrations of the geometric optical phases in physical optics.
Keywords: Optical frame; Spherical flux; Ferromagnetic Heisenberg model; Geometric optical phase